Results of preventive treatment of infertility in productive cows - Suleymanov , M.A.; Kipchakov , Sh.U. (American Journal of Botany and Bioengineering, 2025)
The article describes the clinical signs of infertility in these cows, blood parameters, and the effect of the drug “Multivit+Meniral” and “Microvit” on the normalization of the sexual cycle in cows.